Papaya (Carica papaya L.) juice changes hepatic TNF-α and antioxidant status induced by low dose ionizing radiation in mice/ Wan Mazlina Md Saad... [et al.] - Md Saad, Wan Mazlina; Ngah, Nurul Asyikin; Mohamad Salin, Nur Shafinaz; Mohamad Tajudin, Anati; Abdul Razak, Hairil Rashmizal (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Ionizing radiation has the ability to induce oxidative stress through free radicals formation. Hepatic display multiple functional alterations after ionizing radiations exposure. Papaya (Carica papaya L.) is widely cultivated globally with high antioxidant and anti stimulant activity against oxidative stress. The study was aims to assess the radioprotective effect of 50% papaya juice (Carica papaya L.) in alleviating low dose ionizing radiation-induced oxidative stress in mice hepatic tissue. Eighteen male Balb/c mice were assigned into three equal groups. Negative control group received filtered tap water and normal diet ad libitum, radiation group given filtered tap water and normal diet ad libitium and supplementation group was supplemented with 50% papaya (Carica papaya L.) juice for 28 days. Both radiation and supplementation groups were exposed to 100 µGy gamma radiation on day 29. The activities of superoxide dismutase (SOD), total glutathione (GSH) and TNF-α levels were determined in hepatic tissues. SOD inhibition activity in supplementation group showed highly significant increment in comparison to radiation group (p=0.001), total GSH levels of liver tissue in supplementation group showed significant increment compared to radiation group (p=0.015) and TNF-α levels showed significant differences between positive and supplementation groups (p=0.000). In conclusion, these results postulates that there are significant effect of low-dose ionizing radiation against oxidative stress and inflammation, indicating the protective effects of 50% of papaya (Carica papaya L.) against low dose ionizing radiation induced oxidative stress in mice hepatic tissues.